Comparison of the Ethical Views of Al-Farabi and Al-Ghazali: The Concept of Happiness and Goodness in Islamic Philosophy - Zulmi Aryani; Jamaris; Sulfyarma M (International Journal of Educational and Life Sciences, 2024)
This article discusses a comparative ethical outlook between two great figures in Islamic philosophy, Al-Farabi and Al-Ghazali, focusing on the concepts of happiness and goodness in their teachings. Although both come from different intellectual backgrounds, namely Al-Farabi with a rational and philosophical approach and Al-Ghazali with a spiritual and Sufi orientation, both have significant views on the ultimate goal of human life. This article aims to analyze the similarities and differences in their views regarding the achievement of happiness and goodness, as well as the philosophical implications of their views on human life and Islamic ethics.